Increase Creativity and Ability Student In Following the Learning Process Through Media Unit Length - Salwa Patricia Adjim; Feby Anggriani Husain; Hawadira Haleda; Siti Khumaira Khairunnisa; Abdul Rahmat (Periodica Journal, 2022)
We take title from the unit medium long as our project , because we want to increase interest and knowledge participant educate in following the learning process through the media unit long the . As we know characteristic abstract mathematics along characteristic others who don't simple annoying many less students interested in math . so with that's what we decided for create unit media long with hope that students class V SD can understand with good about method measure unit long and them could more active in follow learning with using unit media long.
Keywords: interest; creativity; Learning